Protective Effect of the Methanolic Extract of Malva parviflora L. leaves on Acetic Acid-induced Ulcerative Colitis in Rats - Dugani, Aisha (Saudi J Gastroenterol, 2016)
BACKGROUND/AIMS: Inflammatory bowel disease (IBD) is a general term describing chronic, idiopathic relapsing, inflammatory conditions of the gastrointestinal tract of unknown etiology. Previous studies have indicated that Malva parviflora leaf extract possesses anti-inflammatory, antioxidant, and antiulcerogenic activity. activity. This work aimed to investigatee the anti-inflammatory effect of the methanolic (MEMP) and aqueous (AEMP) extracts of M. parviflora leaves on acetic acid-induced colitis in rats. MATERIALS AND METHODS: 42 male Wistar albino rats were divided into seven groups (n = 6). Group I: Normal saline control group with no colitis; Group II: Acetic acid colitis group; Group III: 100 mg/kg/5 d MEMP; Group IV: 200 mg/kg/5 d.MEMP; Group V: 100 mg/kg/5 d AEMP; Group VI: 200 mg/kg/5 d AEMP; Group VII: Prednisolone group (2 mg/kg/5 d). Treatments were followed by induction of colitis using intrarectal instillation of 2 mL of 4% acetic acid. Colon damage was evaluated macroscopically (spleen weight/body weight, colon weight/length ratio) and the histological changes were also recorded. RESULTS: The results of this study showed that acetic acid caused severe inflammation of the colon and a significant increase in spleen weight/body weight, and an increase in colon weight/length ratio compared with normal control group. Pretreatment with MEMP and AEMP for 5 days followed by induction of colitis resulted in a significant attenuation of spleen weight and colon weight/length ratio compared with acetic acid control group. Methanolic extract provided better anticolitic effect than aqueous extract; the effect was prominent at the dose of 200 mg/kg. Histopathological findings confirmed the protective effect of the MEMP. CONCLUSION: In conclusion, MEMP could ameliorate mucosal damage in experimentally induced colitis when given orally.